Pass me the ball: narcissism in performance settings. Issue 1 (1st January 2018) - Roberts, Ross; Woodman, Tim; Sedikides, Constantine
ABSTRACT: The performance arena provides a multitude of opportunities for lionizing the self. Narcissistic individuals crave admiration and glory, and thus the performance domain constitutes an ideal medium for researchers to explore narcissistic behavior. However, despite its potential relevance and substantial research history within mainstream psychology, narcissism is only now starting to receive interest from researchers in the sport and performance domain. In this article, we aim to raise the relevance of narcissism (and more generally personality) within performance settings and provide a platform for future research in the area. We review research on the relation between narcissism and performance and conclude that narcissists' performance is contingent upon perceived opportunities for glory. We also offer suggestions for explanatory mechanisms. Further, we examine factors that may influence narcissistic behavior in environments that vary in their opportunity for glory. In addition, as leadership positions present opportunities for glory, we ask whether narcissists make effective leaders. We propose theoretical extensions of the narcissism literature to the performance domain, and we close with a call for greater consideration of the role of personality in performance contexts.